PENGEMBANGAN SISTEM INFORMASI PERPUSTAKAAN BERBASIS WEB DI KAMPUNG EMAS KRAPYAK IX - Wulandari, Catur Nur Agustina; Jati, Handaru (Journal of Information Technology and Education (JITED), 2024)
The development of a web-based library information system in Kampung Emas Krapyak IX aims to manage data on book collections, members, and book lending and return transactions with an information system that ensures its quality in accordance with ISO/IEC 25010 standards in terms of functional suitability, performance efficiency, usability, and reliability. The research method used is Research and Development and the development model follows the Waterfall model. Research instruments for assessing functional suitability use a checklist questionnaire. Performance efficiency is tested using GTMetrix. Usability assessment employs the USE Questionnaire by Arnold M. Lund, and reliability testing uses WAPT 10.1. The research results indicate that the developed system has met the requirements as an information system capable of addressing data management challenges. Furthermore, the developed system has also fulfilled the criteria for functional suitability, performance efficiency, usability, and reliability.